Reproductive Biology Of Mystus Nigriceps From In The Pinang Luar Oxbow Waters Buluh Cina Village, Siak Hulu District, Kampar Regency, Riau Province - Ompusunggu, Siska D; Efizon, Deni; Putra, Ridwan Manda (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
Mystus nigriceps (Bagridae) is a type freshwater fish that live in the tropics which are inhabitants of the waters of the river, oxbow and flood inundation areas in Riau and it is known as carnivor fish. The study aims to understand reproductive biology of M. nigriceps from in The Pinang Luar Oxbow Waters Buluh Cina Village, Siak Hulu District, Kampar Regency, Riau Province, has been conducted on Januari to April 2014. Parameter measured were sex ratio, GSI, maturity level, fecundity , and egg diameter. There were 132 fishes, There were 82 male and 50 female, Total Long of fish was 23-184 mm and the weight of fish was 2-40 gr, which collected and measured. The ratio of male and female 1:0,6. The GSI of the fish was 0,05-5,9%, egg diameter was relative small (0,28-0,38 mm). The fecundity of fish from the Pinang Luar Oxbow Waters was 5925- 11.258 eggs/fish. The water quality shown tremperature range 26 – 28 0C, pH was 5, DO 4,6 – 6,2 mg/l, C02 5,8-8,8 mg/l, brightness 22-49cm, depth 108-520 cm. The water quality of fish. During the sampling periode, the maturity level of the fish geted was various, indicate that the M. nigriceps spawning period is relatively long. It is predicated that the M. nigriceps is parsial spawner.Key words : Mystus nigriceps, Bagridae, GSI, maturity level, and fecundity